2021
DOI: 10.1101/2021.12.02.21267189
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

EpiLPS: a fast and flexible Bayesian tool for near real-time estimation of the time-varying reproduction number

Abstract: In infectious disease epidemiology, the instantaneous reproduction number R(t) is a timevarying metric defined as the average number of secondary infections generated by individuals who are infectious at time t. It is therefore a crucial epidemiological parameter that assists public health decision makers in the management of an epidemic. We present a new Bayesian tool for robust estimation of the time-varying reproduction number. The proposed methodology smooths the epidemic curve and allows to obtain (approx… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The former data stream ignores the reporting delays, while the latter takes these delays into account but ignores the uncertainty associated with the delay dimension. In both scenarios, estimation of R t is carried out using the estimR() routine of the EpiLPS package (Gressani, 2021). To summarize, the simulation study allows to compare three models, namely M 1 providing R t estimates using reported cases only, M 2 providing R t estimates using nowcasted incidence data and M 3 , our proposed model, based on joint modeling of delay and the time-varying reproduction number.…”
Section: Simulation Studymentioning
confidence: 99%
“…The former data stream ignores the reporting delays, while the latter takes these delays into account but ignores the uncertainty associated with the delay dimension. In both scenarios, estimation of R t is carried out using the estimR() routine of the EpiLPS package (Gressani, 2021). To summarize, the simulation study allows to compare three models, namely M 1 providing R t estimates using reported cases only, M 2 providing R t estimates using nowcasted incidence data and M 3 , our proposed model, based on joint modeling of delay and the time-varying reproduction number.…”
Section: Simulation Studymentioning
confidence: 99%
“…Specifically, we fit the following model log(µ t,d ) = 1), where 6 l=1 β l z l (t, d) represents the day of the week with Monday taken as the reference category. Algorithms to fit the model are available within the EpiLPS package (Gressani, 2021) through the nowcasting() routine.…”
Section: Simulationsmentioning
confidence: 99%
“…While the proposed nowcasting model is rather complex, we have coded the nowcasting() routine in the EpiLPS package (Gressani (2021)) to provide a user-friendly experience.…”
Section: Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, Section 5 concludes with a discussion for future research and limitations of our work. A routine reflecting the proposed methodology to estimate the incubation density has been added to the EpiLPS package (Gressani, 2021) and a dedicated repository (https://github.com/oswaldogressani/Incubation) permits to reproduce the results of the manuscript.…”
Section: Introductionmentioning
confidence: 99%